2004
DOI: 10.1002/elps.200305868
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis of biological particles: Viruses, bacteria, and eukaryotic cells

Abstract: A review about the application of electrophoretic methods in the capillary format for the investigation of large biological assemblies like viruses, bacteria, yeast or entire mammalian cells is given. These entities are of a size ranging between some nanometers and tens of micrometers. They can form colloidal solutions or dispersions and move under the influence of an electric field. They are separated by zone electrophoresis according to their different electrophoretic velocity, and characterized by the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
94
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 52 publications
1
94
0
Order By: Relevance
“…Reviews about the analysis of virus particles using electrophoresis in capillaries and microfluidic devices, covering approximately the last 10 years of research in this field, can be found in [1][2][3][4]. The analysis of intact viruses with CE, and even with other analytical separation techniques, is for some reason very scarce, although CE can offer a fast and cheap alternative for the classical virological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews about the analysis of virus particles using electrophoresis in capillaries and microfluidic devices, covering approximately the last 10 years of research in this field, can be found in [1][2][3][4]. The analysis of intact viruses with CE, and even with other analytical separation techniques, is for some reason very scarce, although CE can offer a fast and cheap alternative for the classical virological techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Cell electrophoresis is practically the only method available for estimating the cell surface charge density [3][4][5][6]. Cell electrophoretic mobility (EPM), which can be measured by a cell electrophoresis experiment, is a characteristic physical property that reflects the electrical and mechanical properties of the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, altering the composition and pH of the surrounding solution will affect the electrophoretic mobility of microorganisms [22]. For a more detailed treatment of these concepts, including the theoretical considerations in the study of the colloidal features of microorganisms by CE, interested readers can take resort of some works published on this topic [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%